Ethical issues in funding orphan drug research and development. Issue 3 (28th February 2005) - Gericke, C A; Riesberg, A; Busse, R
Abstract : This essay outlines the moral dilemma of funding orphan drug research and development. To date, ethical aspects of priority setting for research funding have not been an issue of discussion in the bioethics debate. Conflicting moral obligations of beneficence and distributive justice appear to demand very different levels of funding for orphan drug research. The two types of orphan disease, rare diseases and tropical diseases, however, present very different ethical challenges to questions about allocation of research funds. The dilemma is analysed considering utilitarian and rights based theories of justice and moral obligations of non-abandonment and a professional obligation to advance medical science. The limitations of standard economic evaluation tools and other priority setting tools used to inform health policy decision makers on research funding decisions are outlined.